A bio-inspired solution for manufacturing control systems - Leitão, Paulo (2010)
Manufacturing is nowadays facing with markets trends that ask for more customized products, shorter product life-cycles, best quality and shorter prices. Addressing these requirements, manufacturing systems need to be more responsive and reconfigurable, adapting their behaviors to changing conditions. The concepts inherited from biology and nature seem suitable to design reconfigurable manufacturing systems. In this paper, a bio-inspired solution, where self-organization and holonic manufacturing systems play key roles, is described, contributing to achieve an adaptive and evolvable reconfigurable manufacturing control system.